2017
DOI: 10.1080/14789949.2017.1332771
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics related to length of stay in Dutch forensic psychiatric care

Abstract: Create an overview of characteristics of patients in long-term forensic psychiatric care (LFPC) with a higher length of stay (LOS) care compared to patients in regular forensic psychiatric care (RFPC) with a shorter LOS. Data were collected from 139 patient records. This study examined whether patients in LFPC differ from patients in RFPC on sociodemographic data, legal data and clinical data and whether those characteristics are able to predict LOS. Patients in LFPC were more often born in a Dutch Caribbean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 28 publications
7
55
0
Order By: Relevance
“…In recent years, prolonged inpatient treatment in psychiatry in general and forensic psychiatry in particular has faced more and more criticism and scientific scrutiny: Especially within involuntary treatment settings, inappropriately long stays have been viewed as potentially unethical (1)(2)(3)(4)(5)(6). In addition, doubts have been raised about the benefits of prolonged inpatient treatment for patients' rehabilitation (3,7). Prolonged duration of inpatient treatment has been discussed as an indicator of economic inefficiency -particularly for forensic inpatient treatment, which constitutes a low-volume high-cost sector (3,(8)(9)(10)(11)(12)(13)(14).…”
Section: Background and Objectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, prolonged inpatient treatment in psychiatry in general and forensic psychiatry in particular has faced more and more criticism and scientific scrutiny: Especially within involuntary treatment settings, inappropriately long stays have been viewed as potentially unethical (1)(2)(3)(4)(5)(6). In addition, doubts have been raised about the benefits of prolonged inpatient treatment for patients' rehabilitation (3,7). Prolonged duration of inpatient treatment has been discussed as an indicator of economic inefficiency -particularly for forensic inpatient treatment, which constitutes a low-volume high-cost sector (3,(8)(9)(10)(11)(12)(13)(14).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Prolonged duration of inpatient treatment has been discussed as an indicator of economic inefficiency -particularly for forensic inpatient treatment, which constitutes a low-volume high-cost sector (3,(8)(9)(10)(11)(12)(13)(14). The internationally observed prolongation of forensic hospitalizations in the past years (1,3,7,(15)(16)(17), as well as the ever-growing demand for forensic services (18)(19)(20)(21), have become a subject of socio-political debate with urgent need for more research on avenues to reduce the duration of inpatient treatments in order to reduce exploding costs whenever possible (2,4). A recent review of 38 studies in eleven countries summarized a rich set of patient characteristics contributing to length of stay in psychiatric inpatient treatment (6), but concluded that just ten studies were useful in identifying clinically useful predictive factors, since "more rigorous multivariate statistical techniques" are required in order to eliminate confounding factors.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 3 more Smart Citations